Teacher autonomy and motivation in Thai classroom: A self-determination theory perspective - Kaur, Amrita; Awang Hashim, Rosna (UUM Press, 2016)
This monograph investigates the construct of autonomy in eastern settings by reviewing the evidence from debates that originate from both the cultures. Through empirical findings, it helps to look beyond the theories and principles of cross cultural differences. It describes autonomy by focusing on human needs that are innate, universal and essential to all humans, irrespective of their cultural or other differences. We hope that the information provided in this monograph will be insightful for the readers who are interested in the concept of autonomy use in classrooms for better results.